Serotype 2 Streptococcus suis growth inhibition mediated by intraspecies contact-dependent mechanism - Prajiraporn Prasopthum; Jeeraphong Thanongsaksrikul; Onruedee Khantisitthiporn; Pongsri Tongtawe; Buppa Arechanajan; Potjanee Srimanote (Scientific Reports)
Abstract Streptococcus suis is an opportunistic pathogen or pathobionts in pigs and a zoonotic pathogen for humans. S. suis Serotype 2 (SS2) is the predominant serotype isolated from diseased pigs but rarely isolated from healthy pigs. This study aims to investigate whether the growth of SS2 can be inhibited by commensal S. suis non-serotype 2 (non-SS2) sharing tonsillar habitats. Agar co-culture (CI<1.0) and transwell assays confirmed that two non-SS2 strains inhibited the growth of patients, diseased and asymptomatic pig SS2 isolates by contact-dependent mechanism. Kinetic co-culture demonstrated that the consequence of this competition was the coexistence of SS2 at the low density. Moreover, non-SS2 also interfered SS2 adhesion on IPEC-J2 cells. Comparative whole genome analysis elucidated that contact-dependent growth inhibition involved with T7SS homologs and apparently non-lethal interaction. Complete semi-phosphorylative Entner-Doudoroff, CMP-Neu5Ac, and Catechol meta-cleavage pathways distinctively found in non-SS2 and their increased expression during co-culture might facilitate them to outcompete the growth of SS2. In conclusion, this study identified a novel contact-dependent growth competition phenotype in non-SS2 that might contribute to maintaining a low density of the SS2 target in natural habitats.